Analisis Pembiayaan Operasional Sekolah dalam Meningkatkan Mutu Pembelajaran - Suharyanto H. Soro; Ahmad Rifandi; Sayid Khoerul Annas; Sugih Nurezki (LP. Ma'arif Janggan Magetan, 2024)
School operational financing is one of the important aspects in the successful implementation of learning activities in educational units. Proper planning of school financing is not a simple job. This requires the ability to read and respond to environmental changes that occur both in the short and long term. This study aims to analyze and find school operational financing in improving the quality of learning at Cipada 1 Elementary School, including fund allocation, funding sources, and the effectiveness of its use. The researcher used a qualitative research paradigm with a case study approach. The results of the study found that school operational financing carried out with correct and appropriate planning according to needs can improve the quality of learning in educational units. In other words, in general the funds are used to support learning activities, procurement of facilities, and development of teacher competencies.